Adapted Grading in Physical Education for Students with Disabilities. Issue 5 (12th June 2020) - Roth, Kristi
Abstract : An adapted grading system for students with disabilities in general physical education allows utilization of existing assessment tools such as rubrics and checklists and provides methods of individualization and modification based on the student's needs. Adapted grading methods include weighting components of class grades and unit assessments, calculating a level of difficulty score, and establishing supplementary grades including a level of attainment and level of independence grade. All methods discussed provide the general and/or adapted physical educator with strategies for generating valid numerical grades for their students with disabilities. Nontraditional grade reporting methods are also discussed.